Relationships among collagen fiber orientation, mineralization, mineral maturity, and crystallinity. (12th August 2020) - Kimura-Suda, Hiromi; Nakamura, Fumiya; Oseto, Ryota; Kanehira, Yuya; Sato, Dai; Fujita, Ryo; Ota, Masahiro; Takahata, Masahiko
Abstract: Bone quality is a combination of the material and structural properties of bone. Reductions in bone quality parameters, such as the degree of collagen fiber orientation, mineralization, mineral maturity, and crystallinity, affect bone strength. However, the relationships among the bone quality parameters remain poorly understood. In this work, we investigated the relationships among collagen fiber orientation and other bone quality parameters in the rat femur using Fourier transform infrared spectroscopic imaging and infrared dichroism imaging. In cortical bone, collagen fibers were found to be aligned longitudinally and an increase in the degree of mineral maturity or mineralization was associated with an increase in the degree of collagen fiber orientation.